Peran Motivasi Sebagai Variabel Mediasi dalam Pengaruh Pelatihan Terhadap Kinerja Karyawan dalam Kondisi Pandemi Covid-19 Pada PT Jasa Raharja Cabang Sumatera Barat - Muhammad Nurhalim; Rahmi Fahmy (Ekonomis: Journal of Economics and Business, 2021)
At the end of 2019, a case of pneumonia caused by the corona virus was first discovered in the city of Wuhan, China. The disease then began to spread around the world quickly and became known as Covid-19. The Covid-19 pandemic has had a tremendous impact on various aspects of life, one of which is the economic aspect, including the financial condition of various companies. As one of the companies affected by the Covid-19 virus, namely PT Jasa Raharja West Sumatra Branch. Since the Covid-19 virus pandemic, many changes have occurred and various efforts have been made within PT Jasa Raharja's West Sumatra Branch to break the chain of the spread of the Covid-19 virus and also to stabilize the company's financial condition and improve employee performance during the Covid-19 pandemic. some of them by providing training and motivational activities to their employees. This study aims to analyze the effect of training mediated by motivation on employee performance during the Covid-19 pandemic, carried out on 49 permanent employees of PT Jasa Raharja West Sumatra Branch through the distribution of questionnaires, then the data obtained was processed using the SmartPLS software version 3.3. The results of the research conducted, it was found that motivation is proven to have a partially mediating role on the relationship between training and employee performance of PT Jasa Raharja West Sumatra Branch, especially during the Covid-19 pandemic.